Robust HIV-specific immune responses were induced by DNA vaccine prime followed by attenuated recombinant vaccinia virus (LC16m8 strain) boost - Shinoda, Kaori (Clinical immunology (Orlando, Fla.), 2006)
Recombinant vaccinia virus-based vaccine combined with DNA vaccine has produced a protective immune response against HIV infection in non-human primates. In this study, we explored the immunogenicity of a recombinant vaccinia virus (LC16m8 strain), which has been used in children without severe side effects. The vaccinia virus expressing an HIV(89.6)env gene (vLC-Env) alone or combined with a DNA vaccine expressing the HIV(89.6)env gene (pCAG-Env) was characterized in BALB/c mice. Vaccination of vLC-Env induced much higher HIV-specific humoral and cell-mediated immune responses than that of pCAG-Env. Priming with pCAG-Env further enhanced vLC-Env induced immune responses, especially cell-mediated immune response. Moreover, efficient expression of Env protein was achieved following infection of bone marrow dendritic cells by vLC-Env in vitro. Administration of vLC-Env-infected dendritic cells to mice generated a high cell-mediated immune response. These results demonstrate that priming with pCAG-Env and boosting with vLC-Env represents a logical candidate for vaccination against HIV infection